Implementasi Metode Simple Additive Weighting (SAW) Untuk Penentuan Penerima Zakat - Hanggar Wahyu Agi Prayogo; Lailil Muflikhah; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Zakat can be one way done in effort to increase social welfare and was one of the important role in economic community empowerment. Other benefits of zakat is to help reduce poverty and also can reduce the social inequality in society. But the problems encountered by these institutions in distributing zakat is the inaccuracy in choosing a recipient of zakat. The inaccuracy in choosing a zakat recipient occurs because the zakat management agency still provides subjective assessments. It is causing loss to the people who are more eligible to receive the zakat. The SAW (Simple Additive Weighting) is one of the methods in decision support system that can be used to create a system that can determine the recipient of zakat. There are 4 criteria used in determining zakat recipient in this research, there are family status, family income, total dependents and value report card. Based on the accuracy testing that has been done by using 60 test data, obtained the best accuracy of 90%. The SAW method can be applied properly in determining the recipient of zakat.